AKUNTABILITAS DAN TRANSPARANSI PERTANGGUNGJAWABAN ANGGARAN PENDAPATAN BELANJA DESA (APBDes - Hanifah, Suci Indah; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the implementation of accounting and financial management and barriers and efforts that have been made in overcoming barriers to accounting recording and local financial management in the Village of Menganti districk Gresik regency.This research is a descriptive research which is done by using qualitative approach. The primary data and secondary data is used as the source of data. The data collection technique is in the form of field research (field research). The collected data is analyzed by using qualitative descriptive paradigm.The financial management of Kepatihan village has been run on the basis of the Regulation of the Minister of Home Affairs No. 37 of 2007 which shows the accountable and transparent implementation which is reviewed from accountability reporting of Village Budget (APBDesa), but from the accounting recording, further coaching and training is needed, since it has not completely in accordance with the provisions. The main barrier is the lack of effectiveness in the training of local apparatus and the competence of human resources so special and continuous attention from the local village officials is needed.Keywords: Village Budget, Accountabillity and Transparancy.